MANAJEMEN PRODUKSI SANGGAR KIJANG BERANTAI DI KOTA PONTIANAK - Alrinaldi, Alrinaldi; Djau, Nurmila Sari; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by the interest of researcher to examine the management of production in the Kijang Berantai gallery. The purpose of this research was to describe the production management of Kijang Berantai gallery. The method used in this research was descriptive method with a qualitative research form. The approach used in this research was the sociology approach. Data collection techniques in this study used observation, interview and documentation techniques while the data collection tools used in this research were observation guidelines, interview guidelines, camera and notebook. Testing the validity of the data of this research used source triangulation technique. Data analysis techniques in this research were data reduction, data presentation and conclusion drawing. The results of this study indicated that one of the Kijang Berantai gallery programs was to hold dance and music performances performed by implementing art production management so the art performances run smoothly and effectively. Key words: Art Production, Kijang Berantai Gallery, Management